2016
DOI: 10.3109/08820538.2015.1115255
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Mediators in Stevens–Johnson Syndrome and Toxic Epidermal Necrolysis

Abstract: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are a spectrum of T-cell mediated immune disorders. While the contributory mechanisms leading to the apoptosis of epidermal cells in SJS/TEN remain unproven, the keratinocyte apoptosis seen in SJS/TEN is thought to occur through the T-cell mediated Fas-Fas ligand (FasL), perforin/granzyme B, and other immune mediators. Most recently, emphasis has been placed on the granulysin pathway as being the primary mediator of apoptosis and widespread ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 66 publications
1
8
0
1
Order By: Relevance
“…The results of clinical and histopathological studies suggest that TEN is a specific hypersensitive immune response induced by drugs. Cytotoxic T lymphocyte is the main effector cells, cytotoxic proteins such as cell membrane receptor molecules Fas and its ligand Fasl, perforin and cytokine TNF-α play an important role [5][6]. Our patient had a high levels of IL-2R, IL-6, IL-10 and TNF-α, which supported above studies.…”
Section: Discussionsupporting
confidence: 87%
“…The results of clinical and histopathological studies suggest that TEN is a specific hypersensitive immune response induced by drugs. Cytotoxic T lymphocyte is the main effector cells, cytotoxic proteins such as cell membrane receptor molecules Fas and its ligand Fasl, perforin and cytokine TNF-α play an important role [5][6]. Our patient had a high levels of IL-2R, IL-6, IL-10 and TNF-α, which supported above studies.…”
Section: Discussionsupporting
confidence: 87%
“…The use of systemic corticosteroids, intravenous immunoglobulins, and tumor necrosis factor (TNF)-alpha inhibitors have all been described in the acute phase, with mortality results varying from improved mortality, no benefit, to increased mortality. 5,20,24 Recent data on cyclosporine, however, includes a report that compared cyclosporine to other systemic therapies, and found that cyclosporine reduced mortality in SJS/TEN patients. 25 A recently published systematic review of treatment of SJS/TEN in the acute phase also reported a significant benefit of cyclosporine.…”
Section: Supportive Medical Carementioning
confidence: 99%
“…Complete re-epithelialization was reached in a week (Figure 1d 3 | DISCUSSION SJS/TEN are a spectrum of rare, acute, and life-threatening delayedtype drug hypersensitivity reactions that are most commonly caused by drugs and, rarely, infections. The conditions are characterized by extensive skin necrosis, epidermal detachment, and involvement of mucous membrane, which typically occur within 1-3 weeks after the administration of the suspected drugs (Saeed & Chodosh, 2016). Antibiotics, anticonvulsants, and nonsteroidal anti-inflammatory drugs are the main triggers of this severe dermatosis (Gubinelli, Canzona, Tonanzi, Raskovic, & Didona, 2009).…”
Section: Case Reportmentioning
confidence: 99%